2020
DOI: 10.1177/0306624x20981041
|View full text |Cite
|
Sign up to set email alerts
|

Situational and Individual Risk Factors for Cybercrime Victimization in a Cross-national Context

Abstract: Routine Activity Theory (RAT) and the general theory of crime have been widely employed to understand cybercrime victimization. However, there is a need to integrate these theoretical frameworks to better understand victimization from a cross-national perspective. A web-based survey was conducted among participants aged 15 to 25 years from the U.S., Finland, Spain, and South Korea. Factors related to RAT were associated with increased victimization in all four countries although results varied between the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 71 publications
3
25
0
1
Order By: Relevance
“…The second most prevalent was sexual victimization by adults, followed by victimization to online sexual harassment and to other cybercrime. The cybercrime prevalence rates are in line with the earlier international research literature on cybercrime victimization among adolescents and young adults (Keipi et al, 2017;Mikkola et al, 2020). We also found that ODA use was associated with more likely sexual harassment victimization, sexual victimization both by adolescents and peers, and cybercrime victimization, and that this relationship is driven by risky online activities.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The second most prevalent was sexual victimization by adults, followed by victimization to online sexual harassment and to other cybercrime. The cybercrime prevalence rates are in line with the earlier international research literature on cybercrime victimization among adolescents and young adults (Keipi et al, 2017;Mikkola et al, 2020). We also found that ODA use was associated with more likely sexual harassment victimization, sexual victimization both by adolescents and peers, and cybercrime victimization, and that this relationship is driven by risky online activities.…”
Section: Discussionsupporting
confidence: 90%
“…These results add to previous research investigating various forms of youth victimization. For instance, previous crossnational research has found that youth in Finland, Spain, South Korea, and the United States have similar prevalence rates when it comes to cybercrime victimization: 7% in the United States, 4% in South Korea, 8% in Finland, and 7% in Spain (Mikkola et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found high neuroticism, extroversion, and openness, as well as low agreeableness and conscientiousness to be associated with cybervictimization (ElSherief et al, 2018;Kowalski et al, 2012;Peluchette et al, 2015). Impulsivity has also been tied to offline and online victimization among adolescents and young adults (Álvarez-García et al, 2019;Bossler & Holt, 2010;Fanti et al, 2012;Kokkinos et al, 2014;López-Larrañaga & Orue, 2019;Mikkola et al, 2021;Pratt et al, 2014;Vazsonyi et al, 2012) and among the adult population (Nedelec, 2018). Impulsivity is related to co-occurring victimization both offline and online (Nedelec, 2018).…”
Section: Risk Factors and Consequences For Victimsmentioning
confidence: 98%
“…RAT focuses on risk factors of victimization and states that individuals' everyday routines can put them at risk of becoming targets of crimes by exposing them to dangerous circumstances. In the online context, a target's visibility is one of the most crucial factors (Choi & Lee, 2017;Mikkola et al, 2021;Näsi et al, 2017), and for that reason, it is part of our focus in this article as well. Harassment may take place anywhere online, but social media sites are the most common places where such victimization occurs (Pew Research Center, 2021).…”
Section: Risk Factors and Consequences For Victimsmentioning
confidence: 99%